2021 Social Accounting Matrix for Okara District, Pakistan - International Food Policy Research Institute; International Water Management Institute (International Food Policy Research Institute, 2025)
The 2021 Social Accounting Matrix for Okara District, Pakistan (SAM) dataset is part of an initiative to improve subnational economic modeling and policy analysis in Pakistan. The open-access version of the dataset disaggregates domestic production across key sectors with a special focus on agriculture and food systems. Factors of production include labor, land, and capital. Labor is further disaggregated by sector and skill level, where data allow. Households are categorized by rural and urban residence and by income or expenditure group, based on available survey data. Additional accounts include enterprises, government, taxes, savings-investment, and rest of the world to capture inter-institutional and inter-regional flows.